Inflammatory loops in the epithelial–immune microenvironment of the skin and skin appendages in chronic inflammatory diseases - Dainichi, Teruki; Iwata, Masashi (Frontiers in Immunology, 2023)
The epithelial–immune microenvironment (EIME) of epithelial tissues has five common elements: (1) microbial flora, (2) barrier, (3) epithelial cells, (4) immune cells, and (5) peripheral nerve endings. EIME provides both constant defense and situation-specific protective responses through three-layered mechanisms comprising barriers, innate immunity, and acquired immunity. The skin is one of the largest organs in the host defense system. The interactions between the five EIME elements of the skin protect against external dangers from the environment. This dysregulation can result in the generation of inflammatory loops in chronic inflammatory skin diseases. Here, we propose an understanding of EIME in chronic skin diseases, such as atopic dermatitis, psoriasis, systemic lupus erythematosus, alopecia areata, and acne vulgaris. We discuss the current treatment strategies targeting their inflammatory loops and propose possible therapeutic targets in the future.